ANALYSIS PENGARUH JOB STRESS, JOB SATISFACTION, DAN JOB MOTIVATION TERHADAP WORKFORCE PRODUCTIVITY - Danang Prihandoko; Sisca Putri Wulandari; Dewi Kurniawati; Tasya Riuna (Pascasarjana Universitas Halu Oleo, 2019)
The purpose of this study was to determine the significant effect of job stress, job satisfaction and job motivation on workforce productivity in PT. XYZ. That Workforce Productivity, useful to increase the productivity, can be found in PT. XYZ. The research method that we use is a survey method by filling in a questionnaire that we spread directly to test subjects, who are PT. XYZ’s employees. This research was conducted using SmartPLS tools.The factors that we develop based on early research are level of job stress, job satisfaction and job motivation on employees. The result of this research explain that three of indepent variable, overall in this research take significant effect to dependent variable in range 30%, while the rest 70% is affected by another variables which can’t be mention in this research.Keywords: Job Satisfaction, Job Stress, Job Motivation, Workforce Productivity.